Composite mica paper

By screening and crushing mica blocks, mixing copper-silicon-aluminum alloy powder and silicone, and scribing and hot pressing, composite mica paper is prepared, which solves the problems of easy tear, poor surface gloss, poor weather resistance, poor opening and poor adhesion of existing mica papers, and achieves high strength, good electrical properties and temperature resistance.

CN116905274BActive Publication Date: 2025-04-18浙江荣泰电工器材股份有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310855994.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-07-13
Publication Date
2025-04-18
Estimated Expiration
2043-07-13

AI Technical Summary

Technical Problem

Existing mica papers are prone to tear, have poor surface gloss, poor weather resistance, poor opening and poor adhesion.

Method used

Mica pulp was prepared by screening mica blocks, crushing and grading, and mixing copper-silicon-aluminum alloy powder, silicone and surface modifier, and scribing and hot pressing to prepare composite mica paper.

Benefits of technology

The basic mechanical properties, electrical properties and temperature resistance of composite mica paper are improved, its bonding properties are improved, and the tensile strength and dielectric strength are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure GDA0005261787900000071
    Figure GDA0005261787900000071
  • Figure GDA0005261787900000072
    Figure GDA0005261787900000072
  • Figure GDA0005261787900000081
    Figure GDA0005261787900000081
Patent Text Reader

Abstract

The present invention belongs to the technical field of mica paper processing, and specifically relates to composite mica paper. The mica paper is made of alloy powder, mica pulp and organosilicon as a paper base, and the obtained paper base material is further subjected to hot pressing modification treatment by a surface modifier to form a composite mica paper. In the technical scheme of the present invention, the particle size distribution treatment of mica powder and copper-silicon-aluminum alloy powder components makes the surface density of the prepared mica paper good, and the toughness is significantly improved, and the copper-silicon-aluminum alloy powder, organosilicon and surface modifier work synergistically to improve the mechanical properties of the mica paper, so that the composite mica paper has physical properties such as high volume density and high tensile strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of mica paper processing, and in particular relates to composite mica paper. Background Art

[0002] Mica is a naturally occurring layered silicate mineral, and its crystal structure is composed of two layers of silicon-oxygen tetrahedrons sandwiching a layer of aluminum-oxygen octahedrons. Generally speaking, the bond between silicon-oxygen tetrahedrons and aluminum-oxygen octahedrons is relatively strong, while the link between the supplementary positive ion layer and the two compound silicon-oxygen layers is relatively weak, and the mica crystal can be easily peeled apart along the plane where the positive ions are located.

[0003] Mica has complete flakes and can be peeled into extremely thin layers. It has excellent physical and electrical properties and can maintain the above properties at high temperatures. It is completely chemically inert and non-flammable, and is widely used in electronics, aviation, transportation, instrumentation and other industrial sectors, as well as defense and cutting-edge industrial fields. However, the utilization rate of mica in the process of processing mica ore into mica products is too low. In order to make full use of broken mica resources, mica paper came into being. Mica paper is a common industrial packaging material, which is mainly used for packaging electronic products.

[0004] Existing mica paper has some defects: the tensile strength of mica paper is generally not high, and it is easy to be torn during use and packaging, affecting the packaging quality; the mica sheet filling amount is low, and the strength of the mica paper itself is insufficient, which is easy to produce tearing during use and cutting, and also leads to poor surface gloss; mica paper is mainly made of pulp, and is easy to deform and age after being affected by external factors such as weather for a long time; there are gaps between mica sheets, and the opening and adhesion properties are poor. Summary of the invention

[0005] In order to solve the problems of easy tearing, poor surface gloss, poor weather resistance, poor opening and poor adhesion of existing mica paper, the present invention provides composite mica paper and specifically describes its preparation technology scheme.

[0006] The objects of the present invention are:

[0007] 1. Improve the basic mechanical properties of composite mica paper;

[0008] 2. Ensure the electrical properties and temperature resistance of composite mica paper;

[0009] 3. Improve the bonding properties of composite mica paper.

[0010] To achieve the above objectives, the present invention adopts the following technical solutions.

[0011] Composite mica paper, the composite mica paper is prepared by the following process:

[0012] (1) Screening raw materials: mica blocks;

[0013] (2) crushing and grading: the mica blocks screened in step (1) are subjected to hydraulic crushing and graded filtration to obtain mica slurry;

[0014] (3) pulping and papermaking: mixing copper-silicon-aluminum alloy powder, organosilicon, and organic solvent in proportion until uniformly dispersed to form a mixture, adding the mixture to the mica slurry obtained in step (2) and stirring evenly, and papermaking to obtain a mica paper base;

[0015] (4) Casting, drying, and hot pressing: coating the surface modifier on the mica paper base obtained in step (3), drying and hot pressing to obtain composite mica paper, and then cutting according to process requirements.

[0016] The thickness of the mica block in step (1) is ≤0.30 mm.

[0017] The hydraulic crushing in step (2) is to crush the mica into mica powder using high-pressure water.

[0018] The mica powder of 60-100 mesh is obtained by graded filtration in step (2), and water is injected to prepare mica slurry with a viscosity of 100-200 mPa·s.

[0019] The ratio in step (3) refers to the mass ratio of copper-silicon-aluminum alloy powder, organic silicon, and organic solvent being (4-8):

[0020] (1~3):(10~15).

[0021] The mixed material in step (3) is 30-50wt% of the mica slurry.

[0022] The copper-silicon-aluminum alloy powder in step (3) has a rare earth oxide mass fraction of 3-5wt%, a silicon mass fraction of 12-28wt%, a copper mass fraction of 20-30wt%, and the remainder is aluminum. The copper-silicon-aluminum alloy powder has a particle size of 50-70μm.

[0023] As a preference,

[0024] The rare earth oxide in the copper-silicon-aluminum alloy powder in step (3) is cerium oxide.

[0025] The organosilicon in step (3) is vinyl-terminated polydimethylsiloxane.

[0026] As a preference,

[0027] The organosilicon in step (3) is a long-chain polymer vinyl-terminated polydimethylsiloxane with a weight average molecular weight of 26,000 to 30,000.

[0028] As a preference,

[0029] The organic solvent in step (3) is tetrahydrofuran.

[0030] As a preference,

[0031] In step (3), the papermaking is a process in which the slurry passes through a papermaking machine and is evenly hung on a net by the intermolecular force and electrostatic attraction of the mica powder to form paper.

[0032] The mica paper base in step (3) has a basis weight of 80 to 160 g / m 2 .

[0033] As a preference,

[0034] The surface modifier in step (4) is dimethyl sulfoxide and / or cationic chitosan.

[0035] As a preference,

[0036] The ratio of dimethyl sulfoxide to cationic chitosan in step (4) is 1 mL: (0.1-0.3) g.

[0037] The coating amount of the coating process in step (4) is 10-20 g / m 2 After coating, place the mica paper base on the panel and allow the solvent to evaporate for a period of time before coating again. The target coating amount is 45-90g / m 2 .

[0038] As a preference,

[0039] The drying in step (4) is carried out at 85-100° C. for 2-3 hours until the moisture content of the mica paper does not exceed 0.3wt%. When the temperature is too high, the mica paper is prone to fall off the cylinder and bubble. When the temperature is too low, the mica paper will stick to the drying cylinder.

[0040] As a preference,

[0041] The hot pressing in step (4) is to apply a pressure of 1.5 to 2.5 MPa to the dried mica paper at 160 to 200° C. and maintain the pressure for 10 to 15 minutes.

[0042] The thickness of the composite mica paper in step (4) is 0.1 to 0.20 mm.

[0043] In the technical solution of the present invention, the thickness of the mica block is ≤0.30mm, and this thickness can ensure that most of the mica can be hydraulically crushed into mica powder with a large diameter-to-thickness ratio. When mica powders of different particle sizes are used to make mica paper, they affect the directionality of the mica powder in the mica paper, and then affect the internal porosity, tensile strength, dielectric strength and other properties of the material. With the increase of the content of mica powder with large particle size, the thickness of the mica paper increases first and then decreases, and the tensile strength and dielectric strength of the mica paper increase first and then decrease. Moreover, mica powder with small particle size can be used as a filler, and synergistically acts with copper-silicon-aluminum alloy powder to enhance the interlayer bonding effect.

[0044] In order to obtain mica powder of appropriate particle size, the present invention adopts hydraulic crushing method. Hydraulic crushing does not destroy the crystal structure and physical properties of mica. Because the mica is dissociated and peeled along the cleavage plane under the impact of water, the obtained mica powder has a smooth surface and a large diameter-to-thickness ratio. At the same time, the particle sizes of mica powder, copper-silicon-aluminum alloy powder and silicone are reasonably matched to form a close accumulation of solid phase, increase the strength of composite mica paper and reduce its cracks.

[0045] The addition of copper-silicon-aluminum alloy powder does not directly improve the performance of mica paper. Some aluminum compounds diffuse into the mica paper base and interact with the silicon-oxygen tetrahedron and aluminum-oxygen octahedron contained in the mica itself to enhance the dielectric strength. This is because when the aluminum compound content is insufficient, it cannot form an effective spatial structure with the mica paper base to form a cross-linked network. Affected by air, the mica paper base has poor dielectric strength. However, due to the high density of aluminum compounds, they are easily precipitated in silicone, affecting the ductility of silicone. At the same time, since aluminum oxide is bound to silicone through The solvent diffuses between the mica paper layers and its distribution is uneven, resulting in a decrease in the electrical properties of the mica paper, so the alumina content should not be too high; in addition, Si and Al can form a eutectic system. When the Si content exceeds 12wt%, it can improve the wear resistance of the mica paper, increase its density, and reduce the problems of high-temperature thermal cracking and excessive volume shrinkage. However, when the Si content exceeds 28wt%, long strips of eutectic silicon will appear in the hypereutectic system, which will seriously reduce the mechanical properties of the mica paper, and the local eutectic silicon is too hard, making the mica paper difficult to cut.

[0046] Cu is added to the hypereutectic high silicon aluminum alloy. Cu plays a role of solid solution strengthening in the system, and also produces intermetallic compound phase and eutectic structure with other alloy elements. As a strengthening phase and wear-resistant phase in the alloy, it can effectively improve the hardness and strength of the pressed mica paper. When silicone contacts the surface of Cu, silane loses hydrogen atoms to form a weak Cu-Si bond, which is easily attacked by water molecules and further reacts. Due to the low catalytic activity of Cu, the reaction speed of silicone is slow, and it is difficult to form large-sized microspheres. Due to the entanglement and connection of polymer molecular chains, the interlayer structure is tight; but excessive addition of Cu is easy to cause component segregation, making the alloy performance uneven, and seriously reducing the corrosion resistance of the alloy.

[0047] In addition, rare earth oxides have the characteristics of high melting point and high specific gravity. The addition of an appropriate amount of cerium oxide can not only refine the alloy grains, but also form needle-shaped precipitation phases to improve the wear resistance of the alloy. However, excessive cerium oxide causes a large amount of peeling of mica paper when it is subjected to wear, which is directly related to the large amount of precipitation phases.

[0048] On the other hand, vinyl-terminated polydimethylsiloxane has Si-O-Si as the main chain and its Si-O bond energy is high, which makes the mica paper surface have good temperature resistance. However, silicone has poor toughness at high temperatures, so the present invention considers toughening and modifying silicone. The mica paper has a spatial structure between layers. During the subsequent hot pressing process, the copper-silicon-aluminum alloy powder and silicone are dispersed in the solvent and diffused into the spatial structure. The -C=C- in the silicone reacts with the Si-H bond to produce silylation, which synergistically improves the tensile strength, wear resistance and other mechanical properties of the mica paper with the surface modifier.

[0049] In practical applications, mica paper is easily cracked by repeated loading or unloading of thermal stress at high temperatures, resulting in peeling of the mica paper layers. Therefore, toughness consideration is particularly important. Cationic chitosan has a flexible long chain and can form a film with good toughness, which can enhance the toughness of mica paper. In addition, dimethyl sulfoxide inhibits the granulation of cationic chitosan.

[0050] In addition, after the mica block is peeled, the interlayer K + The ions are dissolved, the negative charge on the surface is neutralized, and it is easy to form hydrogen bonds and ionic bonds with the active groups. The tensile strength of the produced mica paper is improved. On this basis, the mica paper is hot pressed at a high temperature of 160-180°C and a pressure of 1.5-2MPa. The interlayer spacing is reduced, and the surface modifier diffuses into the mica paper interlayer. The metal ions in the spatial structure are coated with flexible long chains to produce intermolecular forces, and its structure is more stable.

[0051] The beneficial effects of the present invention are as follows:

[0052] (1) The particle size distribution of mica powder and copper-silicon-aluminum alloy powder components is reasonable, the surface density is good, and the fracture of mica paper under dielectric testing is greatly reduced;

[0053] (2) The copper-silicon-aluminum alloy powder, organic silicon and surface modifier work synergistically to improve the mechanical properties of mica paper, so that the composite mica paper has physical properties such as high volume density and high tensile strength;

[0054] (3) Copper-silicon-aluminum alloy powder is added between the mica paper layers, and the mica paper has high dielectric strength. DETAILED DESCRIPTION

[0055] The present invention is further described in detail below in conjunction with specific embodiments. Those of ordinary skill in the art will be able to implement the present invention based on these descriptions. In addition, the embodiments of the present invention involved in the following description are generally only embodiments of a part of the present invention, rather than all embodiments. Therefore, based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work should fall within the scope of protection of the present invention.

[0056] Unless otherwise specified, the raw materials used in the examples of the present invention are all commercially available or available to those skilled in the art; unless otherwise specified, the methods used in the examples of the present invention are all methods known to those skilled in the art.

[0057] Unless otherwise specified, the vinyl-terminated polydimethylsiloxane used in the embodiments of the present invention is a commercially available product with an average molecular weight of 28,000.

[0058] Example 1

[0059] Composite mica paper is prepared by the following process:

[0060] (1) Screening mica blocks with a thickness of ≤0.30 mm by a thickness screening machine;

[0061] (2) crushing the mica screened in step (1) by high-pressure water hydraulic crushing, filtering by graded filtration to obtain mica powder with a particle size of 60 to 80 mesh, respectively, and injecting water to prepare mica slurry with a viscosity of about 150 mPa·s;

[0062] (3) Take 60 μm copper-silicon-aluminum alloy powder, in which the mass fraction of cerium oxide is 4wt%, the mass fraction of silicon is 24wt%, the mass fraction of copper is 24wt%, and the mass fraction of aluminum is 48wt%, then mix the copper-silicon-aluminum alloy powder, vinyl-terminated polydimethylsiloxane and tetrahydrofuran in a mass ratio of 6:3:15 until they are uniformly dispersed, and then mix the mixture with the mica slurry obtained in step (2) in a mass ratio of 1:2, and make it into 100 g / m 2Mica paper base;

[0063] (4) Dimethyl sulfoxide and cationic chitosan were mixed in a ratio of 1 mL:0.2 g to prepare a surface modifier, and a single 15 g / m 2 The amount of the mica paper base obtained in step (3) is applied to the mica paper base. After coating, the mica paper base is placed on the panel to allow the solvent to evaporate for a period of time before the next coating. The target coating amount is 60g / m 2 , dried at 85°C for 3h, and applied a pressure of 2MPa to the dried mica paper at 180°C for 10min to obtain a composite mica paper with a thickness of 0.15mm.

[0064] The obtained composite mica paper is made of alloy powder, mica pulp and organic silicon as a paper base, and the obtained paper base material is further subjected to hot pressing modification treatment with a surface modifier.

[0065] The basis weight is 160g / m 2 The composite mica paper was cut into rectangles with a length of 120 mm and a width of 20 mm and tested for surface quality, tensile strength, dielectric strength, and volume resistivity. The results are shown in the following table.

[0066]

[0067] Example 2

[0068] The composite mica paper, compared with Example 1, has a different particle size of mica powder and is prepared by the following process:

[0069] (1) Screening mica blocks with a thickness of ≤0.30 mm by a thickness screening machine;

[0070] (2) crushing the mica screened in step (1) by high-pressure water hydraulic crushing, filtering by graded filtration to obtain mica powder with a particle size of 80 to 100 mesh, respectively, and injecting water to prepare mica slurry with a viscosity of about 150 mPa·s;

[0071] (3) Take 60 μm copper-silicon-aluminum alloy powder, in which the mass fraction of cerium oxide is 4wt%, the mass fraction of silicon is 24wt%, the mass fraction of copper is 24wt%, and the mass fraction of aluminum is 48wt%, then mix the copper-silicon-aluminum alloy powder, vinyl-terminated polydimethylsiloxane and tetrahydrofuran in a mass ratio of 6:3:15 until they are uniformly dispersed, and then mix the mixture with the mica slurry obtained in step (2) in a mass ratio of 1:2, and make it into 100 g / m 2 Mica paper base;

[0072] (4) Dimethyl sulfoxide and cationic chitosan were mixed in a ratio of 1 mL:0.2 g to prepare a surface modifier, and a single 15 g / m2 The amount of the mica paper base obtained in step (3) is applied to the mica paper base. After coating, the mica paper base is placed on the panel to allow the solvent to evaporate for a period of time before the next coating. The target coating amount is 60g / m 2 , dried at 85°C for 3h, and applied a pressure of 2MPa to the dried mica paper at 180°C for 10min to obtain a composite mica paper with a thickness of 0.15mm.

[0073] The prepared composite mica paper was subjected to the same test as in Example 1, and the results are shown in the following table.

[0074]

[0075]

[0076] It can be clearly seen from the above test results that the composite mica paper prepared by mica powder with large particle size has higher mechanical strength. Because the particle size of mica powder is large, the tensile strength of mica paper is better, and the tensile strength is increased from 25.7N / cm to 29.14N / cm, an increase of 13.4%, and the dielectric strength is increased from 188.93kV / mm to 201.92kV / mm, an increase of 6.9%, and the volume resistivity is increased by 2.9%. Under the same conditions, the mica paper prepared by mica powder with slightly larger particle size has better surface quality, and when the alloy powder fills the pores, the dielectric strength of the composite mica paper is higher.

[0077] Example 3

[0078] The composite mica paper is prepared by the following process, in which the ratio of mica slurry, copper-silicon-aluminum alloy powder and vinyl-terminated polydimethylsiloxane is changed compared with Example 2:

[0079] (1) Screening mica blocks with a thickness of ≤0.30 mm by a thickness screening machine;

[0080] (2) crushing the mica screened in step (1) by high-pressure water hydraulic crushing, filtering by graded filtration to obtain mica powder with a particle size of 80 to 100 mesh, respectively, and injecting water to prepare mica slurry with a viscosity of about 150 mPa·s;

[0081] (3) Take 60 μm copper-silicon-aluminum alloy powder, in which the mass fraction of cerium oxide is 4wt%, the mass fraction of silicon is 24wt%, the mass fraction of copper is 24wt%, and the mass fraction of aluminum is 48wt%, then mix the copper-silicon-aluminum alloy powder, vinyl-terminated polydimethylsiloxane and tetrahydrofuran in a mass ratio of 6:3:15 until they are uniformly dispersed, and then mix the mixture with the mica slurry obtained in step (2) in a mass ratio of 0.6:2, and make it into 100 g / m 2 Mica paper base;

[0082] (4) Dimethyl sulfoxide and cationic chitosan were mixed in a ratio of 1 mL:0.2 g to prepare a surface modifier, and a single 15 g / m 2 The amount of the mica paper base obtained in step (3) is applied to the mica paper base. After coating, the mica paper base is placed on the panel to allow the solvent to evaporate for a period of time before the next coating. The target coating amount is 60g / m 2 , dried at 85°C for 3h, and applied a pressure of 2MPa to the dried mica paper at 180°C for 10min to obtain a composite mica paper with a thickness of 0.15mm.

[0083] The prepared composite mica paper was subjected to the same test as in Example 1, and the results are shown in the following table.

[0084]

[0085] From the above characterization results, it can be seen that the tensile strength of the composite mica paper decreased by 5.7%, the dielectric strength decreased by 4.8%, and the volume resistivity decreased by 4.3% compared with Example 2. This indicates that the copper-silicon-aluminum alloy powder between the layers is reduced, resulting in the incompleteness of the spatial structure, the components are segregated in the mica paper, and cannot be evenly distributed, which weakens its electrical properties.

[0086] Comparative Example 1

[0087] Composite mica paper, based on Example 1, only makes the following adjustments:

[0088] The step (2) is changed to the step (1) of crushing the mica screened by high-pressure water hydraulically, filtering by graded sieves to obtain mica powder with a particle size of 40 to 60 mesh, respectively, and injecting water to prepare mica slurry with a viscosity of about 150 mPa·s.

[0089] The prepared composite mica paper was subjected to the same test as in Example 1, and the results are shown in the following table.

[0090]

[0091] It can be seen from the above test results that compared with Example 1, the tensile strength of mica paper made from mica powder with a small particle size is reduced by 14.9%. The reason is that mica powder with too small a mesh size reduces the effective contact area between powders and increases the distance between mica powders, which is not conducive to improving the tensile strength of mica paper.

[0092] Comparative Example 2

[0093] Composite mica paper, based on Example 1, only makes the following adjustments:

[0094] The proportion of the copper-silicon-aluminum alloy powder was changed to 52% by mass of aluminum, 24% by mass of silicon, and 24% by mass of copper.

[0095] The prepared composite mica paper was subjected to the same test as in Example 1, and the results are shown in the following table.

[0096]

[0097] It can be seen from the above characterization results that compared with Example 1, the tensile strength of the composite mica paper decreased by 4.1%, and its surface was rougher. The reason is that cerium oxide has the advantages of being both hard and hydrophobic, which can improve the wear resistance of mica paper.

[0098] Comparative Example 3

[0099] Composite mica paper, based on Example 1, only makes the following adjustments:

[0100] The long-chain polymer vinyl-terminated polydimethylsiloxane is replaced with a short-chain polymer vinyl-terminated polydimethylsiloxane, whose weight average molecular weight is only 2000.

[0101] The prepared composite mica paper was subjected to the same test as in Example 1, and the results are shown in the following table.

[0102]

[0103] It can be seen from the above characterization results that compared with Example 1, the tensile strength of the composite mica paper decreased by 27.4%, the dielectric strength decreased by 8.3%, and the volume resistivity decreased by 7.8%. The reason is that the flexible long-chain structure of vinyl-terminated polydimethylsiloxane can inhibit the diffusion of ions, reduce the chemical bonding density, and absorb external impact force.

[0104] Comparative Example 4

[0105] Composite mica paper, based on Example 2, only makes the following adjustments:

[0106] After drying for 3 h in step (4), the mixture was cooled to room temperature and a pressure of 2 MPa was applied and maintained for 10 min.

[0107] The prepared composite mica paper was subjected to the same test as in Example 1, and the results are shown in the following table.

[0108]

[0109] It can be seen from the above characterization results that compared with Example 2, the tensile strength, dielectric strength and volume resistivity of the composite mica paper are slightly reduced. The reason is that the copper-silicon-aluminum alloy powder and silicone are dispersed in the solvent, and the surface modifier diffuses into the mica paper layer. The powders are combined during the hot pressing process to form a Cu-Si-Al structure. At the same time, due to the high temperature and high pressure, the system undergoes silicon hydrogen addition to produce flexible long chains. The long chains in the silicone and the surface modifier work synergistically to form a multi-layer cross-linked structure in the spatial structure. The metal ions are coated by the flexible long chains to produce intermolecular forces, and the structure is more stable, which makes up for the poor mechanical strength defects of some composite mica papers during application.

[0110] Comparative Example 5

[0111] Composite mica paper, based on Example 2, only makes the following adjustments:

[0112] No surface modifier was added.

[0113] The prepared composite mica paper was subjected to the same test as in Example 1, and the results are shown in the following table.

[0114]

[0115] From the above results, it can be seen that dimethyl sulfoxide and cationic chitosan have a modification effect on the composite mica paper. Since water contains a large number of ions, it can replace the K in the mica paper. + ions, resulting in an increase in the interlayer spacing and repulsion, which in turn leads to a decrease in its tensile strength. However, dimethyl sulfoxide and cationic chitosan can effectively remove ions in water and increase the binding force between mica powders.

Claims

1. Composite mica paper, characterized in that: The mica paper is made of alloy powder, mica pulp and organosilicon as a paper base, and the obtained paper base material is further subjected to hot pressing modification treatment by a surface modifier to form a composite mica paper; The preparation method of the composite mica paper comprises: 1) Take mica raw materials, crush and sieve them to make mica slurry; 2) adding the alloy powder and the organosilicon into an organic solvent and dispersing them evenly to form a mixture, and mixing the mixture evenly with the mica slurry prepared in step 1) to form a mica paper base; 3) coating the surface of the mica paper base obtained in step 2) with a surface modifier, and subjecting the surface to a hot-pressing modification treatment and pressing the surface to a predetermined thickness, thereby obtaining a composite mica paper; in: Step 2) the alloy powder is copper-silicon-aluminum alloy powder; The copper-silicon-aluminum alloy powder has a rare earth oxide mass fraction of 3-5 wt%, a silicon mass fraction of 12-28 wt%, a copper mass fraction of 20-30 wt%, and the remainder is aluminum; Step 2) the organosilicon is vinyl terminated polydimethylsiloxane; The mass ratio of the alloy powder, organic silicon and organic solvent is (4-8): (1-3): (10-15); The amount of the mixed material is 30-50 wt% of the mica slurry; Step 3) the surface modifier is dimethyl sulfoxide and cationic chitosan; The ratio of dimethyl sulfoxide to cationic chitosan is 1 mL: (0.1-0.3) g; Step 3) When the surface modifier is coated on the surface of the mica paper base, the single coating amount is 10 to 20 g / m 2 , dry and then apply the next coating, the total coating amount is 45 ~ 90 g / m 2 .

2. The composite mica paper according to claim 1, characterized in that: Step 1) The mica raw material is crushed and sieved into 60-100 mesh mica powder, and water is added to prepare mica slurry with a viscosity of 100-200 mPa·s.

3. The composite mica paper according to claim 1, characterized in that: Step 2) The mica paper base is made with a basis weight of 80 to 160 g / m 2 .

4. The composite mica paper according to claim 1, characterized in that: Step 3) The hot pressing modification treatment controls the hot pressing temperature to 160-200°C and the pressure to 1.5-2.5 MPa, and maintains the pressure for 10-15 min.

Citation Information

Patent Citations

  • Mica concentrating flux plate preparation method

    CN111484275A

  • High-strength anti-seismic mica plate and forming method

    CN113963873A